Exploring Language Sound and Structures - Sarwandi Kasmei; Nazry Nasyifa; Muhammad Haidir Akbar Filah; Yani Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This journal article offers a thorough examination of language sounds and structures with a special emphasis on the complex interaction between phonetics and phonology. The study looks into how various grammatical structures and sound systems are used by various languages to improve communication and convey meaning. The study starts with a look at the basic units of language sounds, called phonemes, and explores the many articulatory processes involved in their generation. It investigates how phonetic traits like voicing, prosody, and place and manner of articulation contribute to the wide variety of sounds between languages.Furthermore, the article analyzes the organization and patterning of sounds within languages, highlighting the role of phonology. It explores phonological processes such as assimilation, dissimilation, and metathesis, which shape the sound structure of words and sentences. The study also discusses the importance of phonotactics, examining constraints on the combination and sequencing of sounds within a language. The research extends beyond the phonetic and phonological aspects of language to encompass larger linguistic structures. It investigates the syntax, morphology, and semantics of different languages, exploring how words are combined to form meaningful phrases and sentences. The study also examines grammatical phenomena such as agreement, tense, and aspect, shedding light on the ways in which languages express temporal and relational information. The article also examines how language change and language acquisition affect the sounds and structures of languages. It examines how sociolinguistic influences, such as dialectal variation, linguistic contact, and language evolution, have shaped and changed linguistic systems over time. This journal article provides a thorough overview of language sounds and structures, emphasizing how phonetics, phonology, and other linguistic elements interact. The research advances our knowledge of the complexity and diversity of human language, as well as how sounds and grammatical structures are employed to convey meaning and promote effective communication.